Optimization and Implementation of Efficient and Universal Quantum Key Distribution - Da-jun Huang; Wen-zhe Zhong; Jin Zhong; Dong Jiang; Hao Wu (Journal of Electrical and Computer Engineering)
Since quantum key distribution (QKD) can provide proven unconditional security guaranteed by the fundamental laws of quantum mechanics, it has attracted increasing attention over the past three decades. Its low bit rate, however, cannot meet the requirements of modern applications. To solve this problem, recently, an efficient and universal QKD protocol based on chaotic cryptography and middleware technology was proposed, which efficiently increases the bit rate of the underlying QKD system. Nevertheless, we find that this protocol does not take the bit errors into account, and one error bit may lead to the failure of the protocol. In this paper, we give an optimized protocol and deploy it on a BB84 QKD platform. The experimental results show that the optimized version provides resistance to bit errors compared with the original version. And the statistical properties of the generated bits are fully assessed using different methods. The evaluation results prove that the proposed protocol can generate bits with outstanding properties.